(untitled) (The Research of Medical Science Review, 2025)
Background: Birth asphyxia remains a leading cause of neonatal morbidity and mortality, particularly in low- and middle-income countries. Identifying maternal, obstetric, and fetal risk factors is crucial for developing targeted interventions to reduce its incidence. Objective: This study aimed to assess the prevalence of birth asphyxia and its associated risk factors among term neonates at a tertiary care hospital. Methods: A retrospective cohort study was conducted at the Pediatrics and Gynecology & Obstetrics Departments of Khyber Teaching Hospital and Hayatabad Medical Complex, Peshawar, from January 2022 till December 202 Data from 2,500 term neonates were analyzed, including maternal, obstetric, and fetal variables. Birth asphyxia was defined as an Apgar score <7 at 5 minutes, need for positive pressure ventilation, or evidence of hypoxic- ischemic encephalopathy (HIE). Univariate and multivariate logistic regression analyses were performed to identify independent risk factors. Results: The prevalence of birth asphyxia was 10% (n=250). Maternal hypertension (aOR=2.2, 95% CI: 1.6–3.0), inadequate antenatal care (aOR=2.5, 95% CI: 1.8–3.5), prolonged labor (aOR=2.4, 95% CI: 1.7–3.4), and meconium-stained amniotic fluid (aOR=3.0, 95% CI: 2.2–4.1) were significant independent risk factors. Cesarean section (aOR=2.0, 95% CI: 1.5–2.8) and low birth weight (aOR=2.3, 95% CI: 1.6–3.3) were also associated with increased risk. Conclusion: Maternal hypertension, inadequate antenatal care, prolonged labor, and meconium-stained amniotic fluid are key risk factors for birth asphyxia in term neonates. Strengthening antenatal care, improving intrapartum monitoring, and timely intervention are essential to reduce the burden of birth asphyxia and its associated complications.